A study of application of western strategic planning model for small medium entrepreneurs in northern states of Malaysia - Cheng, Wei Hin; Bohari, Abdul Manaf (Asian Economic and Social Society, 2012)
The study examined whether small medium enterprise (SME) in the northern states of Malaysia do strategic planning and if they do, does the Wheelen and Hunger model ( 2008) applies so them .A total of 108 respondents which were from SMEs in Perlis, Kedah and Penang are participated in this research.Results of the study showed that SMEs do have strategic planning and more than half said that their strategic planning process resembled the strategic planning model of Wheelen and Hunger (2008).The strategic planning process of the SMEs was not much different from that of the Wheelen and Hunger (2008) model.